Climate change impact on dam infrastructure and Water Resource - Ilmi, Abu Dedo (Journal of Sustainable Infrastructure, 2025)
Dams are indispensable infrastructures that serve multiple purposes, including water supply, irrigation, hydropower generation, flood control, and recreation. Historically, they have significantly contributed to socioeconomic development by stabilizing water resources and mitigating the risks associated with natural water variability. However, the intensifying impacts of climate change threaten the functionality and resilience of these critical infrastructures. Global climate systems are undergoing significant transformations, including rising temperatures, shifting precipitation patterns, and an increasing frequency and intensity of extreme weather events. These changes present unprecedented challenges for both existing and planned dam infrastructure. This paper provides a comprehensive review of the impacts of climate change on dam infrastructure and water resources, emphasizing the structural vulnerabilities, operational challenges, and adaptive strategies required to enhance climate resilience. The findings aim to inform policymakers, engineers, and water resource managers on strategies to ensure sustainable water management under evolving climatic conditions